The Experience of Systemic Transformation in Contemporary Biographical Narratives of Older Poles - Życzyńska-Ciołek, Danuta (Qualitative Sociology Review, 2019)
The aim of this article is to explore whether—from the subjective perspective of people born before the end of WWII—systemic transformation brought about significant changes in their individual lives, and if yes—what was the meaning of those changes for them. In particular, I examine how experiences related to the events that preceded systemic transformation in Poland or took place during its most intensive stage are reflected in contemporary biographical narratives of 49 persons aged 72 or more, for whom the period of professional activity, in whole or in major part, occurred in the times of the Polish People’s Republic. I perform the analysis in three steps. First, I investigate the place of systemic transformation in the narratives, and consider the reasons why it is relatively often absent or poorly reflected there. Second, I present thematic motifs prevailing in those interviews where references to the systemic change appear. In the third step, I investigate the meaning of experiences connected with transformation for the narrators, the accompanying emotions—some of them still persisting—and ways in which the narrators incorporated those experiences into their biographies. The underlying narratives come from people who were drawn for a nationwide quantitative panel survey many years ago, in 1987, and participated in it for the next 25-30 years.